Acupuncture combined with pelvic floor rehabilitation training for postpartum stress urinary incontinence: protocol for a systematic review and meta-analysis - Wenming, Chu; Xiaoman, Deng; Ling, Gao; Yun, Li; Xiyan, Gao (Frontiers in Medicine, 2023)
Introduction The purpose of this study is to systematically evaluate the efficacy and safety of acupuncture combined with pelvic floor rehabilitation training in the treatment of postpartum stress urinary incontinence, and to promote the further promotion and application of acupuncture in the field of rehabilitation. Methods and analysis Randomized controlled trials (RCTs) of acupuncture combined with pelvic floor rehabilitation in the treatment of postpartum stress urinary incontinence will be searched in PubMed, Web of Science (WOS), Cochrane Library, EMBASE, China National Knowledge Infrastructure (CNKI), Chinese Biomedical Literature Database (CBM), Wanfang (WF), and VIP databases. The clinical trial Registry (ClinicalTrials.gov and Chinese clinical trial Registry) will also be searched. The search period is limited to July 1, 2023, and the language limit of this systematic review is Chinese and English. The primary outcome is clinical effective rate. International Consultation on Incontinence Questionnaire-Short Form (ICI-Q-SF), 1-h pad test, pelvic floor muscle potential value, incidence of adverse events are secondary outcomes. A meta-analysis will be performed using RevMan 5.4 statistical software. If feasible, subgroup analysis and sensitivity analysis will be performed to address potential causes of inconsistency and heterogeneity. The risk of bias will be assessed using the approach recommended by Cochrane Handbook for Systematic Reviews of Interventions, and the quality of evidence will be assessed using GRADE. This Protocol has been developed in accordance with the guideline of Preferred Reporting Items for Systematic review and Meta-Analysis Protocols (PRISMA-P) 2015. Discussion Acupuncture combined with pelvic floor rehabilitation training can effectively promote the rehabilitation of postpartum stress urinary incontinence patients, and provide a reference for the clinical application of integrated Chinese and Western medicine treatment in the field of rehabilitation. Systematic review registration PROSPERO CRD42023455801.